2023
DOI: 10.3390/cimb45030156
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Some Benzo[g]Quinazoline Derivatives as Antiviral Agents against Human Rotavirus Wa Strain: Biological Screening and Docking Study

Abstract: Globally, rotavirus (RV) is the most common cause of acute gastroenteritis in infants and toddlers; however, there are currently no agents available that are tailored to treat rotavirus infection in particular. Improved and widespread immunization programs are being implemented worldwide to reduce rotavirus morbidity and mortality. Despite certain immunizations, there are no licensed antivirals that can attack rotavirus in hosts. Benzoquinazolines, chemical components synthesized in our laboratory, were develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In addition, it is used to explore the interactionsof ligands within the receptor- or putative enzyme-binding sites ( Al-Suwaidan et al, 2015 , Alanazi et al, 2016 ). The selected compounds and co-crystallized inhibitors were subjected to molecular docking at the protein-binding sites to ensure docking accuracy and validation ( Hamdi et al, 2022a , Hamdi et al, 2022b , Abuelizz et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is used to explore the interactionsof ligands within the receptor- or putative enzyme-binding sites ( Al-Suwaidan et al, 2015 , Alanazi et al, 2016 ). The selected compounds and co-crystallized inhibitors were subjected to molecular docking at the protein-binding sites to ensure docking accuracy and validation ( Hamdi et al, 2022a , Hamdi et al, 2022b , Abuelizz et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Quinoline and quinazoline are heterocyclic moieties with well-reported antiviral properties. During investigation of a potential drug to control the pandemic caused by SARS-CoV2, it has been found that RNA-dependent RNA polymerase (RdRp) has a pivotal viral life cycle and quinoline and quinazoline derivatives not only inhibit RNA virus-like HIV-1, Ebola virus, Influenza virus but also shows activity against DNA viruses such as HSV (Herpes simplex virus) and Hepatitis B virus [ 78 82 ]. In continuation of exploring this moiety, Zhao et al synthesized 101 quinoline and quinazoline derivatives and on screening using a cell-based assay, it was found that the inhibition activity shown by the compounds are 5e = 95.03%, 5h = 92.85%, and 5i = 74.94%.…”
Section: Antiviral Schiff Basesmentioning
confidence: 99%